2004
DOI: 10.1139/y04-054
|View full text |Cite
|
Sign up to set email alerts
|

Barosensitive neurons in the rat tractus solitarius and paratrigeminal nucleus: a new model for medullary, cardiovascular reflex regulation

Abstract: The nucleus of the solitary tract (NTS), a termination site for primary afferent fibers from baroreceptors and other peripheral cardiovascular receptors, contains blood pressure-sensitive neurons, some of which have rhythmic activity locked to the cardiac cycle, making them key components of the central pathway for cardiovascular regulation. The paratrigeminal nucleus (Pa5), a small collection of medullary neurons in the dorsal lateral spinal trigeminal tract, like the NTS, receives primary somatosensory input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…Examples include the IX–X and lingual nerves (Figure 1 ), the superior laryngeal nerve and receptive areas surrounding the fauces ( 13 , 16 , 19 26 ), and the sensory inputs from the muscles of mastication ( 27 , 28 ) and molar teeth ( 26 , 29 ). These studies on projections from primary afferent fibers and other studies ( 30 32 ) suggest Pa5 may have a role in ingestion. Others, however, showed that cardiorespiratory activity influences Pa5 ( 30 , 33 ).…”
Section: Anatomy Of the Rostral Mdhsupporting
confidence: 63%
See 1 more Smart Citation
“…Examples include the IX–X and lingual nerves (Figure 1 ), the superior laryngeal nerve and receptive areas surrounding the fauces ( 13 , 16 , 19 26 ), and the sensory inputs from the muscles of mastication ( 27 , 28 ) and molar teeth ( 26 , 29 ). These studies on projections from primary afferent fibers and other studies ( 30 32 ) suggest Pa5 may have a role in ingestion. Others, however, showed that cardiorespiratory activity influences Pa5 ( 30 , 33 ).…”
Section: Anatomy Of the Rostral Mdhsupporting
confidence: 63%
“…These studies on projections from primary afferent fibers and other studies ( 30 32 ) suggest Pa5 may have a role in ingestion. Others, however, showed that cardiorespiratory activity influences Pa5 ( 30 , 33 ). Whether Pa5 is a separable entity or a dissociated component of another nucleus is unknown, but its translucent appearance resembles that of the substantia gelatinosa of the MDH (laminae I and II) as well as the gelatinous nucleus tractus solitarii.…”
Section: Anatomy Of the Rostral Mdhsupporting
confidence: 63%
“…Whether these differential responses relate to the nodose and jugular afferent circuits described herein is not known, but conceivably possible. Furthermore, studies from other laboratories have already demonstrated vagal afferent inputs from some baroreceptor afferents terminate in the Pa5 playing a role in cardiovascular control (Junior et al, 2004 ) and it is intriguing to speculate that these may also be of jugular ganglia origin.…”
Section: Discussionmentioning
confidence: 99%
“…The ventral paratrigeminal nucleus receives somatosensory afferents from trigeminal nerves innervating the nose, cornea, and anterior facial skin (Shigenaga et al, 1986 ; Panneton, 1991 ; Hollandsworth et al, 2009 ). In contrast, the dorsal paratrigeminal nucleus receives trigeminal, glossopharyngeal and vagal inputs (Shigenaga et al, 1986 ; Panneton, 1991 ; Saxon and Hopkins, 2006 ) and is involved in baroreceptor reflexes and cardiovascular regulation (De Sousa Buck et al, 2001 ; Yu and Lindsey, 2003 ; Junior et al, 2004 ). Neurons within the ventral MDH and paratrigeminal nucleus show an increase in the number of Fos-positive neurons, and thus are activated, both during repetitive trained diving in conscious animals (present study; McCulloch, 2005 ; Panneton et al, 2012a ) and nasal stimulation in anesthetized animals (Dutschmann and Herbert, 1997 ; McCulloch and Panneton, 1997 ; Rybka and McCulloch, 2006 ).…”
Section: Discussionmentioning
confidence: 99%